Whole rock and mineral chemistry of the rare metals-bearing mylonitic rocks, Abu Rusheid borehole, south Eastern Desert, Egypt. (December 2022) - Saleh, Gehad M.; Kamar, Mohamed S.; Lasheen, El Saeed R.; Ibrahim, Ibrahim H.; Azer, Mokhles K.
Abstract: Abu Rusheid area represents one of the typical rare metals-bearing rocks in the Northern Neoproterozoic Arabian-Nubian Shield. The current work reports a new detailed lithologic description, petrographic, and mineralogical studies integrated with a geochemical investigation of the borehole no.5 to discern the petrological features, rare metals enrichment and their origin. Abu Rusheid mylonitic rocks are composed mainly of quartz, K-feldspars (Or62-98), plagioclase (Ab98-99), primary muscovite, and neoformed biotite of annite type as well as some accessories such as zircon, columbite, tantalite, fluorite, allanite, xenotime, monazite, and kasolite. They have a noticeable high content of rare earth elements and a conspicuous enrichment of Zr (up to ∼ 4400 ppm), Nb (up to ∼ 2150 ppm), Ta (up to ∼ 270 ppm), Hf (up to ∼ 190 ppm), Zn (up to ∼ 5600 ppm), U (up to ∼ 175 ppm), Pb (up to ∼ 900 ppm) and Th (up to ∼ 1000 ppm) trace elements. REE patterns revel M-type tetrad effect (t1) with an absence of the W-type tetrad segment in the third tetrad (t3). Further constrains, lambda method (where τ2 can be detected) yield a positive values of τ1 (av. 0.534), τ2 (0.487), τ3 (0.498) and τ4 (0.28) for the examined rocks, reflecting M-type tetrads. The rare metals enrichment are related to magmatic as well as the extrusion of lamprophyre dykes yielding alteration processes that led to the remobilization and enrichment of these elements through joints, faulting and their deposition along contacts with the ophiolitic mélange. Highlights: Abu Rusheid (borehole) represent one of the typical rare metals-bearing rocks. Abu Rusheid rocks have a conspicuous Zr, U, Th, Nb, Ta and REEs enrichment. The drilled borehole (45 m depth) rocks reveal variations in trace and REEs. Irber and lambda methods reveal M-type tetrad effects.